If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -1x) + -2(3x + -4) = -1(16 + -1x) (3 * 4 + -1x * 4) + -2(3x + -4) = -1(16 + -1x) (12 + -4x) + -2(3x + -4) = -1(16 + -1x) Reorder the terms: 12 + -4x + -2(-4 + 3x) = -1(16 + -1x) 12 + -4x + (-4 * -2 + 3x * -2) = -1(16 + -1x) 12 + -4x + (8 + -6x) = -1(16 + -1x) Reorder the terms: 12 + 8 + -4x + -6x = -1(16 + -1x) Combine like terms: 12 + 8 = 20 20 + -4x + -6x = -1(16 + -1x) Combine like terms: -4x + -6x = -10x 20 + -10x = -1(16 + -1x) 20 + -10x = (16 * -1 + -1x * -1) 20 + -10x = (-16 + 1x) Solving 20 + -10x = -16 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 20 + -10x + -1x = -16 + 1x + -1x Combine like terms: -10x + -1x = -11x 20 + -11x = -16 + 1x + -1x Combine like terms: 1x + -1x = 0 20 + -11x = -16 + 0 20 + -11x = -16 Add '-20' to each side of the equation. 20 + -20 + -11x = -16 + -20 Combine like terms: 20 + -20 = 0 0 + -11x = -16 + -20 -11x = -16 + -20 Combine like terms: -16 + -20 = -36 -11x = -36 Divide each side by '-11'. x = 3.272727273 Simplifying x = 3.272727273
| 8y=6(y+2.50) | | 7x+5=-15+3x | | 6(3+3x)-4=122 | | 2x-12=o | | 5/4=1-1/4 | | 75=15(2x+1) | | x^3+2x^2-20x+24=0 | | 2(3x+4)+5(3x-5)=3(x-7)+8 | | 3x+2=2x+x-1 | | 7x(2x+3)=56 | | p^2+x^2y^2q^2=x^2z^2 | | 5=6p | | 6+2x-1=9x+7-6x | | 3d+5+17= | | x(y+2)+y=1 | | 2(3x-1)=3x-2 | | x-x*0.1=500 | | 9y-9y^2-2=0 | | t-1.5=5 | | 7(x-1)-(x-4)=8x-1 | | 4+1/4+0.75=x | | (2x+9)+(-3x+9)= | | 25x^3-4x^2-150x+150=0 | | 5x+7-3x-2=4x-1 | | 5x*7-3x-2=4x-1 | | 8x^2+14x-5=0 | | X-(360-x)=124 | | 48=9W-W | | X+10.4=12.2 | | H-18=11 | | 6x+36=3x+76 | | z^2+(z+3)i+1=0 |